ANALISIS MODEL KOMUNIKASI AISAS (ATTENTION, INTEREST, SEARCH, ACTION DAN SHARE) PADA BEAUTY PLATFORM (STUDI KASUS: BRAND SOMETHINC DI FEMALE DAILY) - Aisyah, Trisnina Luthfi; Alfikri, Muhammad (Jurnal Indonesia : Manajemen Informatika dan Komunikasi, 2023)
A digital platform can become an informational medium and public communication in various purposes such as the marketing process. As for one concept that can be applied on the marketing process, it uses AISAS model (Attention, Interest, Search, Action and Share). This study aims to knowing the application of AISAS model on the brand Somethinc through Female Daily. In this study, the methods are to use a qualitative method with a descriptive approach, a case study method and post-positivism paradigm. The data is drawn through interviews with the experienced informan in using the female daily, such as on YouTube, Instagram, Apps and Female Daily Sites. The results obtained from this study describes that the model of AISAS can fill all of the information and communication needed by the masses.